Hubungan Antara Motivasi Berprestasi Dengan Flow Akademik Pada Mahasiswa - Nur Azizah, Egista; Rima Wilantika (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2025)
When a person is in an academic flow, they are able to focus completely and become totally engaged in the task at hand because they enjoy and find comfort in studying. This research objective was to determine the positive correlation between achievement motivation and academic flow among the students of X University in Lampung. This research used a quantitative approach with a sampling technique using simple random sampling. The population in the study were students from X University in Lampung, with a total sample of 128 students from various study programs at X University. The data analysis used is product-moment correlation involving SPSS 25. The results of the product moment correlation indicate that there is a correlation between academic flow and achievement motivation of rxy= 0.999 with p = 0.000 (p < 0.01). This analysis leads to the conclusion that the researcher's hypothesis that is, that there is a positive and significant correlation between academic flow and accomplishment motivation among students at the X University in Lampung is true. The effective contribution of accomplishment motivation to academic flow, which is 99%, supports this result.